The gut microbiome as a potential predictive biomarker for breast cancer: emerging association and geographic differences - Oh, Byeongsang; Lamoury, Gillian; Carroll, Susan; Morgia, Marita; Boyle, Frances; Pavlakis, Nick; Clarke, Stephen; Guminski, Alexander; Menzies, Alexander; Diakos, Connie; Moore, Katrina; Baron-Hay, Sally; et al. (Frontiers in Oncology, 2025)
BackgroundThe gut microbiome may influence breast cancer (BC) development by modulating estrogen metabolism, immune responses, and microbial metabolites. Altered microbial patterns have been reported in BC, but their value as predictive biomarkers remains uncertain.MethodsWe reviewed 13 case–control studies that compared gut microbiome composition in women with and without BC, focusing on diversity, compositional shifts, and geographic variation.ResultsReduced microbial richness (alpha diversity, the number and balance of bacterial species) was observed in more than half of the studies, although findings were not uniform. Differences in community composition (beta diversity) were common. Across studies, BC was consistently associated with elevated Bacteroides and reduced Faecalibacterium, a genus linked to anti-inflammatory effects. Other recurrent findings included enrichment of Eggerthella and Blautia in BC, though results for several taxa were inconsistent. Geographic variation was evident: Eggerthella was enriched in U.S. cohorts, Blautia in European cohorts, and in Chinese cohorts, Prevotella was elevated while Akkermansia was reduced.ConclusionsDespite heterogeneity, converging evidence supports reduced diversity and shifts in select taxa, particularly enrichment of Bacteroides and depletion of Faecalibacterium, as emerging features of the BC microbiome. Geographic differences underscore the influence of host and environmental factors. These findings suggest biomarker potential but highlight the need for larger, longitudinal, and standardized studies to establish causality and clinical utility.